Effect of Leadership on Employee’s Performance Mediated by Cultural Organization, Work Commitment and Motivation - Sappe, Syahruddin; Rante, Yohanis; Tuhumena, Ruben; Bharanti, Bonifasia Elita (Journal of Economics and Behavioral Studies, 2016)
Main mission of regional autonomy is intended to improve the quality of public services and the welfare of the community, creating efficiency and effectiveness of human resource management, as well as empowering and creating a space for people to participate actively in the development process. Therefore, it needs a leader who act can generate commitment, motivation and optimism in carrying out the work, foster an atmosphere of cooperation, and can affect the behavior of subordinates who have an impact on improving the performance of employees. This study aims to identify and assess the relevance of leadership on employee performance mediated by organizational culture, work commitment and work motivation as determinants of employee performance improvement. The sample used in this study was 160 respondents to the analysis unit employees in Food Security Council Keerom Papua Province. Data was collected by questionnaires followed by in-depth interviews. Quantitative Data Analysis using Structural Equation Modeling (SEM) with the help of the program Analysis Moment Structures (AMOS). The results of this study indicate that, good leadership can improve employee performance, when considering the factors that come into play that organizational culture, work commitment and motivation work to DKP in Keerom Papua Province. Furthermore, the results of this study that the strengthening of organizational culture and high employee commitment can lead to increased motivation.